Experimental and numerical investigation of the damage state of Ti-6Al-4V alloy sheet in the tensile test, hydraulic bulging, and hydroforming processes - Yapan, Yusuf Furkan; Korkmaz, Habip Gokay; Toros, Serkan; Turkoz, Mevlut (SPRINGER LONDON LTD, 2024)
There has not been any damage prediction using Johnson-Cook's (JC) hardening and damage model in the hydraulic bulging (HB) and hydroforming (HF), which are the advanced manufacturing processes, of the Ti-6Al-4V (Ti64) alloy. In the presented study, the damage behavior of the Ti64 alloy sheet in the HB and HF processes was investigated both experimentally and numerically for the first time to address the existing research gap. In this context, firstly, tensile tests (TT) were carried out on samples with different stress triaxiality values at three different tensile speeds, and the fracture morphologies of the samples were examined to evaluate whether it was appropriate to use the JC hardening and damage model. Since the fracture surfaces generally exhibit a ductile fracture morphology and are affected by stress triaxiality and strain rate, it was determined that it would be appropriate to use the JC hardening model and damage criterion to predict the damage of the Ti64 alloy in finite element analysis (FEA). Then, JC model parameters were determined by fitting the stress-strain curve obtained from the FEA and experimental tensile tests. In the HB experiments, bulging height and thickness thinning were predicted by FEA with an accuracy of 97% and 96.85%, respectively. In the HF experiments, the experimental burst pressure, die inlet radius, and base radius were predicted correctly at a rate of 92.5%, 95.5%, and 97.8%, respectively. Also, the thickness of the sample showed good agreement with the FEA results. The fracture zones in each process exhibited good agreement with the experimental results. Thus, it has been demonstrated that the JC damage criterion can be successfully applied in FEA if the Ti64 titanium alloy is damaged in various processes.
Keywords: Damage; Fracture morphology; Hydroforming; Johnson-Cook; Ti-6Al-4V; FINITE-ELEMENT SIMULATION; STRAIN-RATE; STRESS TRIAXIALITY; FAILURE BEHAVIOR; TI-6A1-4V ALLOY; TITANIUM; TEMPERATURE; FORMABILITY; MODEL; VALIDATION; Automation & Control Systems; Engineering